Management of gastrointestinal complaints in differentiated thyroid cancer patients treated with 131I - Mirzababaee, M.; Shafiei, B.; Seifollahi, S.; Motazdian, M.; Fatholahi, L.; Delavari, S.; Naghshine, R.; Baharfar, N.; Tabeie, F.; Javadi, H.; Assadi, M.; Asli, I. N. (Nuklearmedizin - NuclearMedicine, 2014)
Objective: To compare safety and efficacy of pantoprazol , metoclopramide, ondansetron, as compared to placebo, in controlling gastrointestinal (GI) complaints of thyroid cancer patients treated with I-131these patients. Design: Four-armed, parallel group, single blind, randomized controlled clinical trial, setting: A university hospital, registration: database for clinical trials IRCT2013061713705N1. Patients: 85 patients with differentiated thyroid cancer who received 131I. Main outcome measures: Post- radioiodine nausea and vomiting within three days of therapy (primary endpoint); occurrence of adverse reaction. Results: The patients’ characteristics were similar within the study groups. Among the study variables, age, sex, administered dosage, history of previous GI complaints, and history of hyper- emesis gravidarum in female patients were not statistically different among the groups (p > 0.05). The results revealed that only ondansetron shows a therapeutic benefit over the placebo in controlling nausea (p < 0.05); however, it does not prevent vomiting (p > 0.05). The other two drugs, pantoprazole and metoclopramide, did not control nausea (p > 0.05) or vomiting (p > 0.05). Conclusions: This study may demonstrate that the therapeutic dose of ondansetron could be an effective prophylactic agent in controlling GI complaints in differential thyroid carcinoma (DTC) patients following RAI therapy; however, these preliminary findings should be validated in larger studies.
Keywords: Differentiated thyroid cancer; gastrointestinal complaint; pantoprazole; metoclopramide; ondansetron